Critical Discussion of Exclusion and Inclusion in CNN Indonesia Online News: Theo Van Leeuwen's View - Ita Putriani; Novia Juita (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2021)
Critical theory is used as a tool to study the problem of clashes between Asmat residents and Fayit Koramil members. Basically, this research emphasizes more attention on Asmat residents who experience marginalization in social life. The purpose of this study was to analyze criminal news under the title "4 Asmat Residents Shot Dead, Kodam Formed an Investigation Team in the CNN Indonesia online news publication Tuesday, May 28, 2019" using Theo van Leuween's theory. Data collection was carried out in three stages, namely (1) reading the news to gain an understanding of the content of the discourse to be examined, (2) marking the news discourse section related to Theo van Leuween's theory, and (3) inventorying sentences related to Theo van Leuween's theory . The approach used in this study is a qualitative approach based on content analysis methods. Based on the results of the study, found two types of exclusions (passivation and nominalization) and three types of inclusions (differentiation, abstraction, and identification). So, it can be concluded in a criminal story entitled "4 Asmat Residents Shot Dead, Kodam Forms an Investigation Team in CNN Indonesia's online news" reporters hiding actors using passive sentences in the headline.